Odpowiedzi

2010-03-10T19:58:27+01:00
A) 4a+4b =4(a+b)
b) 3x+15y =3(x+5y)
c) 7x+14y =7(x+2y)
d) 17x2-17 = 17(x2-1)
e) bc-bd =b(c-d)
f) xy-3x =x(y-3)
g) py-p = p(y-1)
h) 9xy-y = y(9x-1)
i) ab+3b2 = b(a+3b)
2010-03-10T19:58:44+01:00
A)4(a+b)
b) 3(x+5y)
c) 7(x+2y)
d) 17(2x-1)
e) b(c-d)
f) x(y-3)
g) p(y-1)
h) y(9x-1)
i) b(a+6)
2010-03-10T19:58:58+01:00
A) 4a+4b = 4(a+b)
b) 3x+15y = 3(x+5y)
c) 7x+14y = 7(x+2y)
d) 17x2-17 = 17(x²-1)
e) bc-bd = b(c-d)
f) xy-3x = x(y-3)
g) py-p = p(y-1)
h) 9xy-y = y(9x-1)
i) ab+3b2 = b(a+3b)

licze na naj ; )